Intra-arterial bolus octreotide administration during Whipple procedure in patients with fragile pancreas: a novel technique for safer pancreaticojejunostomy. - Konstadoulakis, Manousos M; Filippakis, George M; Lagoudianakis, Emmanuel; Antonakis, Pantelis T; Dervenis, Chris; Bramis, John (J Surg Oncol, 2005)
BACKGROUND AND OBJECTIVES: Leakage from the pancreaticojujenostomy is the most serious complication of Whipple. Pancreatic fistula rate is higher in cases of fragile pancreas often seen in duodenal carcinomas and carcinomas of the ampulla of Vater. Octreotide administration has been used for the prevention of fistula formation through the subcutaneous route. Due to its physiologic effects to the pancreatic parenchyma the intra-arterial administration of octreotide could provide tissue hardening that allows for a technically easier anastomosis while maintaining its protective role for fistula formation. METHODS: Octreotide was injected directly into the distal part of the gastroduodenal artery (GDA) in four patients undergoing Whipple for histologically proven periampullary cancer. RESULTS: Tissue hardening after octreotide administration was evident not only in surgeons' hands but in the intra-operative ultrasound as well. The three patients were discharged on day 9, 11, and 13; they had an uneventful postoperative course, while one patient had a minor bile leak from the choledojejunal anastomosis and was discharged on day 22. CONCLUSIONS: The intra-arterial administration of octreotide during Whipple is a safe procedure and provides tissue hardening thus making the performance of the anastomosis technically easier. The actual benefit in terms of morbidity, mortality, and fistula rate are to be further evaluated.
Keywords: Aged; Ampulla of Vater; Anastomosis, Surgical; Antineoplastic Agents, Hormonal; Common Bile Duct Neoplasms; Cutaneous Fistula; Female; Humans; Injections, Intra-Arterial; Male; Middle Aged; Octreotide; Pancreas; Pancreatic Fistula; Pancreaticoduodenectomy; Pancreaticojejunostomy; Parenteral Nutrition, Total; Postoperative Complications